Hemorrhagic bullae in henoch-schonlein purpura: A case report - Parajuli, S; Paudel, U; Koirala, DP; Ojha, AR (Journal of College of Medical Sciences-Nepal, 2012)
We report a case of ten year old male child of Henoch-Schönlein purpura (HSP) who presented initially with predominant hemorrhagic bullae in extremities. Initial presentation with bullae is rare in HSP. The child recovered within two weeks with a course of systemic and topical steroid without any sequel. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 46-48 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6725